Molecular basis of mucopolysaccharidosis IVA (Morquio A syndrome): A review and classification of GALNS gene variants and reporting of 68 novel variants. Issue 11 (23rd August 2021) - Zanetti, Alessandra; D'Avanzo, Francesca; AlSayed, Moeenaldeen; Brusius‐Facchin, Ana Carolina; Chien, Yin‐Hsiu; Giugliani, Roberto; Izzo, Emanuela; Kasper, David C.; Lin, Hsiang‐Yu; Lin, Shuan‐Pei; Pollard, Laura; Singh, Akashdeep; et al.
Abstract: Mucopolysaccharidosis IVA (MPS IVA, Morquio A syndrome) is a rare autosomal recessive lysosomal storage disorder caused by mutations in the N‐acetylgalactosamine‐6‐sulfatase ( GALNS ) gene. We collected, analyzed, and uniformly summarized all published GALNS gene variants, thus updating the previous mutation review (published in 2014). In addition, new variants were communicated by seven reference laboratories in Europe, the Middle East, Latin America, Asia, and the United States. All data were analyzed to determine common alleles, geographic distribution, level of homozygosity, and genotype‐phenotype correlation. Moreover, variants were classified according to their pathogenicity as suggested by ACMG. Including those previously published, we assembled 446 unique variants, among which 68 were novel, from 1190 subjects (including newborn screening positive subjects). Variants' distribution was missense (65.0%), followed by nonsense (8.1%), splicing (7.2%), small frameshift deletions(del)/insertions(ins) (7.0%), intronic (4.0%), and large del/ins and complex rearrangements (3.8%). Half (50.4%) of the subjects were homozygous, 37.1% were compound heterozygous, and 10.7% had only one variant detected. The novel variants underwent in silico analysis to evaluate their pathogenicity. All variants were submitted to ClinVar (https://www.ncbi.nlm.nih.gov/clinvar/ ) to make them publicly available. Mutation updates are essential for the correct molecular diagnoses, genetic counseling, prenatal and preimplantation diagnosis, and disease management. Abstract : In this mutation update, we collected, analyzed, classified and uniformly summarized all published GALNS gene variants. In addition, 68 new variants were communicated by seven reference laboratories in Europe, the Middle East, Latin America, Asia, and the United States.